2003
DOI: 10.2535/ofaj.80.7
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and Fibroblast Growth Factors (FGFs) in a Three-Dimensional Collagen Gel Culture

Abstract: Summary: Small pieces of mouse aorta were cultured in collagen gels, and the formation of capillary-like tubes from the aortic explant was observed under phase-contrast and transmission electron microscopes. Migration of fibroblastic cells from the aortic explant occurred in 2 days. After about 10 days of culture, capillary-like tubes from the aortic explant were formed in the collagen gels. An immunohistochemical study on the collagen gel culture revealed the expression of fibroblast growth factor 2 (FGF-2) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The present study revealed the up-regulation of FGF-2 following the up-regulation of Egr-1 after both laser and razor injury. In our previous experiment we confirmed the expressions of FGF-9 (Akita et al 2000;Nagatoro et al 2003) and FGF-7 ) during angiogenesis in collagen gels. Pilcher et al (1997) and Miyagi et al (1998) reported that FGF-9 relates to the expression of matrix metalloproteinases (MMPs) and their inhibitors.…”
Section: Discussionsupporting
confidence: 86%
“…The present study revealed the up-regulation of FGF-2 following the up-regulation of Egr-1 after both laser and razor injury. In our previous experiment we confirmed the expressions of FGF-9 (Akita et al 2000;Nagatoro et al 2003) and FGF-7 ) during angiogenesis in collagen gels. Pilcher et al (1997) and Miyagi et al (1998) reported that FGF-9 relates to the expression of matrix metalloproteinases (MMPs) and their inhibitors.…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, exogenous FGF-9 did increase Vegf expression (11). Furthermore, expression of Fgf-9 has been identified in an angiogenic collagen gel culture model, coinciding with the formation of capillary-like tubes (27). The data obtained from our injury model indicated that Fgf-9 regulates vascularization in long bone repair by triggering Vegf expression.…”
Section: Discussionmentioning
confidence: 58%
“…Collagen gel culture has been used widely and effectively for analyzing the biological process of angiogenesis [1013]. Using a three-dimensional (3D) collagen gel culture, we have conducted electron microscopic studies [14, 15] and immunohistochemical studies of fibroblast growth factor- (FGF-) 2 and FGF-9 [16]. Additionally, we have used 3D collagen gel cultures to test angiogenic and anti-angiogenic agents (TNF- α and thalidomide) [17, 18] to study vascular injury after laser microdissection [19] and for profiling of DNA microarray gene expression during angiogenesis [20].…”
Section: Introductionmentioning
confidence: 99%